Web-Based Employee Payment Information System (Case Study at KH.A. Wahab Hasbullah University) - Sufaidah, Siti; Fauziyah, Azizah Nur (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
The application of information technology makes it easier for agencies to carry out data processing activities, including processing employee salary data. The results of observations made at the University of KH. A. Wahab Hasbullah pointed out that employee salary processing is still done manually. Therefore, it is necessary to develop a web-based payroll information system to make it easier for financial admins while preventing data loss. The research was carried out from April to August 2022 using the Waterfall method at KH. A. Wahab Hasbullah University, Jombang. The test results show that the developed employee payroll information system works according to its function and makes it easier for financial admins to make payroll reports.